PSO fined-tuned model-free PID controller with derivative filter for buck-converter driven DC motor - Mohd Zaidi, Mohd Tumari; Amar Faiz, Zainal Abidin; A Shamsul Rahimi, A Subki; Ab Wafi, Ab Aziz; Mohd Ashraf, Ahmad; Mohd Riduwan, Ghazali (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Traditionally, the PID controller parameters are tuned heuristically based on time response behavior of the system. This method is tiresome job and can cause undesirable system response. Therefore, this research suggests the tuning method of a model-free PID controller with derivative filter (PIDF) by implementing Particle Swarm Optimization (PSO). This tuning method is applied to buck-converter driven DC motor control. The speed of DC motor is controlled by PIDF controller. The parameters of PIDF controller are fine-tuned by implementing PSO algorithms. The fitness functions of the algorithm are evaluated based on Sum Square Error (SSE) and Sum Absolute Error (SAE). The state-space representation of buck-converter/DC motor is considered to confirm the design of the control method. The results of the proposed tuning method are compared with PI controller and PIDF controller tuned by PID Tuner Simulink. The time response specifications of angular velocity, armature current and duty cycle input energy are considered as a control scheme performance. Finally, the suggested tuning technique promises a very minimum duty cycle energy and a fast input tracking of DC motor angular velocity.